Impact of Business Planning for Mini Oil Refineries to Enhance Socio-Economic Landscape - Violetta Roshchupkina; Natalia Dimurina; Viktoriya Manuylenko; Natalia Gryzunova; Elena Drannikova; Mukhamed Khamukov (Qubahan Academic Journal)
This article develops a comprehensive business plan for establishing a mini-oil refinery in a Russian Federation territory currently lacking refining capacity. Recognizing the critical need for localized oil processing due to a regional monopoly and the high demand for petroleum products, this study aims to provide a strategic blueprint for potential investors and local authorities. A mixed-methods research design is utilized, combining a systematic literature review of existing business plan frameworks with quantitative data analysis to assess market demand and financial feasibility. The methodologies from UNIDO, EBRD, and TACIS are evaluated for their relevance to the Russian economic and regulatory environment, with UNIDO's framework identified as the most suitable due to its adaptability and comprehensive nature. The findings suggest that implementing a mini-oil refinery is financially viable and aligns with Russian industrial standards. The localized refining capacity significantly enhances regional economic resilience and sustainability by reducing costs, increasing market competition, and creating job opportunities. This study emphasizes the practical significance of the strategic plan, which ensures that effective and efficient operational activities align with the unique demands of the identified territory. This research contributes to the field by offering a practical solution to regional oil refining disparities, promoting economic development, and providing a model for similar contexts. The study’s comprehensive approach and detailed analysis offer valuable insights for policymakers, business planners, and investors in the oil refining industry.